KAJIAN PERLINDUNGAN HUKUM TERHADAP PENYEDIA JASA TRANSPORTASIONLINE DALAM PELAYANAN JASA DALAM PENGANGKUTAN PENUMPANG - Desak Made Rai Ningsih (Universitas Mahendradatta, 2022)
Transportation is one of the derivative needs in society due to economic, social activities, and so on. In general there are two transportations, namely based on conventional and online. But the problem is that discrimination often occurs against providers of online-based transportation services, especially in transporting passengers, so the issue of legal protection and the legal consequences of discriminating against online transportation service providers is a core problem in this research, namely the use of normative legal research methods using primary legal materials, secondary and tertiary as well as using the legislative approach and conceptual approach. The results of this study that the legal protection of online transportation service providers in Indonesia is regulated in legislation including the 1945 Constitution of the Republic of Indonesia which in principle every legal subject must be treated equally before the law, and Law Number 39 Year 1999 which protects that every person is entitled to a job, and legal protection is also contained in Law No. 8 of 1999 which in principle regulates the rights and obligations of business actors. The legal consequence of discrimination is that it can result in criminal and civil law in the form of compensation for imprisonment or fines.